From Collaboration to Transformation: The Mediating Role of Organizational Structure in Madrasah Change Adaptation - Kholilah, Ismatul; Jabar, Cepi Safruddin Abdul; Widian, Agung Purwa (Balai Penelitian dan Pengembangan Agama Semarang, 2025)
The rapid transformations in the educational landscape demand that madrasahs (Islamic schools) develop a strong capacity for adaptation, which is shaped by team learning and the design of organizational structures. This study aims to analyze the influence of team learning on change adaptation, with organizational structure as a mediating variable, and to identify practical implications for the development of madrasahs. The research employed a quantitative approach, using Partial Least Squares Structural Equation Modeling (PLS-SEM), with data collected from madrasah teachers. The analysis reveals that team learning significantly affects change adaptation (β = 0.339, p = 0.006) and exerts a powerful influence on organizational structure (β = 0.827, p = 0.000). Furthermore, organizational structure significantly influences change adaptation (β = 0.529, p = 0.000) and partially mediates the relationship between team learning and change adaptation (β = 0.438, p = 0.000). These findings support the theories of Senge, Mintzberg, Fullan, Teece, and Burnes, which emphasize that team collaboration, adaptive structures, and shared values constitute the foundation of change adaptation. Strengthening team learning, when integrated with organizational restructuring, can accelerate madrasah adaptation to educational dynamics while ensuring the sustainability of innovation and the long-term relevance of these institutions.